Development of platelet lysate based scaffolds from microcapsules for regeneration post-myocardial infarction - Ladeira, Bruno Miguel Fernandes (2021)
As the leading cause of death worldwide, myocardial infarction (MI) carries considerable socioeconomic costs. The damage and clinical complications caused by MI remain unaddressed by current therapeutic strategies. With the advent of tissue engineering and regenerative medicine, novel strategies to promote regeneration of heart muscle are possible. This dissertation focuses on the application of microcapsule-based systems to promote the recovery of damaged tissue. The biofabrication of core-shell microcapsules for the encapsulation of cells and bioactive molecules has been reviewed, along with the contributions of these platforms to the field of regenerative medicine. In this work, coaxial electrospray technology has been used to encapsulate methacryloyl platelet lysate (PLMA) within alginate microcapsules, producing sacrificial templates for the preparation of porous microcarriers. By exposing the capsules to UV light, it was possible to induce the photopolymerization of PLMA. The alginate shell was removed and the resulting particles were subjected to a freeze-drying procedure, producing PLMA microsponges. By adjusting production parameters, the proposed system was able to produce microcapsules with core diameter ranging from 300 to 600 μm, as well as microcapsules with shell thickness below 100 μm. The microsponges prepared with this system were shown to allow cell attachment and promote the assembly of cardiac microtissues, indicating potential applications in tissue engineering.